2017
DOI: 10.20469/ijtes.3.40001-1
|View full text |Cite
|
Sign up to set email alerts
|

Business and IT Alignment in Higher Education Sector

Abstract: Business and IT alignment has been and continues to be a major challenge for researchers and practitioners.Although it has been studied for almost five decades, the complexity of this issue seems to be steadily increasing along with the rapid changes in the business and IT environments. This paper, through a critical review of the literature, aims first to provide an overview of business and IT alignment as a serious and challenging issue that faces business and IT managers in many public and private organisat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Decision-making in these institutions is shared, organizational culture among universities and colleges differs, and academic courses and research activities are independent [17]. According to Alghamdi et al [30], business and IT alignment in the education sector has received the least attention in the business and IT alignment literature compared to other public and private sectors.…”
Section: B Business and It Alignment In Heismentioning
confidence: 99%
See 1 more Smart Citation
“…Decision-making in these institutions is shared, organizational culture among universities and colleges differs, and academic courses and research activities are independent [17]. According to Alghamdi et al [30], business and IT alignment in the education sector has received the least attention in the business and IT alignment literature compared to other public and private sectors.…”
Section: B Business and It Alignment In Heismentioning
confidence: 99%
“…The misalignment between eLearning technologies and HEIs' strategies can lead to a failure in achieving maximum utilization of these technologies to enhance overall teaching and learning activities. Such a challenge in the higher education sector has received the lowest attention in IT alignment research [30], [45]. A real example of misalignment practice that usually occurs in many HEIs is the isolation of implementing IT projects away from the actual needs of students and academic staff.…”
Section: A Awareness Of the Problemmentioning
confidence: 99%
“…Strategic alignment represents a significant challenge in the higher education sector, which has received less attention in research than its enterprise domain counterpart (Alghamdi and Sun, 2017). Additionally, a previous study (Rodríguez-Abitia and Bribiesca-Correa, 2021) demonstrated that ineffective leadership, insufficient cultural changes, limited innovation and financial support negatively impact alignment.…”
Section: To What Degree Do Universities' Strategic Goals and Objectiv...mentioning
confidence: 99%
“…Examples of these are system or mobile applications, websites, and other customized digital products to promote competitive advantages in the marketplace. Business owners/stakeholders should consider implementing or developing technology in their business plan process [4,5]. SMEs are becoming popular trailblazers in technology due to continuous or frequently active connectivity.…”
Section: Background Of the Studymentioning
confidence: 99%